A method for preparing single crystals of quantum magnetic material K2Cu3Ge5O14

CN122773469APending Publication Date: 2026-09-18HUAZHONG UNIV OF SCI & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610845198.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-06-11
Publication Date
2026-09-18

AI Technical Summary

Technical Problem

[0008]针对现有技术的缺陷,本申请的目的在于提供一种量子磁性材料K2Cu3Ge5O14单晶的制备方法,旨在解决现有方法制备的K2Cu3Ge5O14单晶尺寸小、存在杂相,无法满足物性测试和器件应用对晶体要求的问题

Benefits of technology

(1)本申请提供的量子磁性材料K2Cu3Ge5O14单晶的制备方法,以K2CO3、CuO、GeO2作为原料,采用单一KCl作为助熔剂,从源头上彻底避免了P5+等其他阳离子的引入,从而杜绝了K2CuP2O7等含磷杂相的生成,能够制备得到纯相K2Cu3Ge5O14单晶。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122773469A_ABST
    Figure CN122773469A_ABST
Patent Text Reader

Abstract

This application belongs to the field of single-crystal materials technology, and more specifically, relates to a quantum magnetic material K2Cu3Ge5O. 14 A method for preparing single crystals. This method involves mixing raw materials K₂CO₃, CuO, and GeO₂ with a single flux KCl, placing the mixture in a platinum crucible, sealing and heating it at a constant temperature, and then slowly cooling it to precipitate single crystals. After removing the residual flux, millimeter-sized pure-phase K₂Cu₃Ge₅O₂ is obtained. 14 Single crystal. Its process is simple and low-cost, effectively solving the problems of small crystal size and impurity phases in existing processes, meeting the needs of property testing and device applications. Furthermore, the prepared K2Cu3Ge5O 14 Single crystals possess low-dimensional spin band gaps and low-temperature magnetic ordering behavior, making them ideal model materials for studying the quantum magnetism, spin excitation spectrum, and quantum critical behavior of trimer chains. They also have broad application prospects in functional devices such as quantum computing, spintronics, and low-temperature magnetic refrigeration.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application belongs to the field of single-crystal materials technology, and more specifically, relates to a quantum magnetic material K2Cu3Ge5O. 14 Methods for preparing single crystals. Background Technology

[0002] Low-dimensional quantum magnetic materials, due to their strong spin entanglement and significant quantum fluctuations, can generate novel multi-particle entangled states that differ from those in three-dimensional systems. The manipulation of these novel states can be applied to the development of novel quantum devices. Synthesizing high-quality, large-size single-crystal materials is fundamental to observing quantum phenomena and implementing quantum spin state manipulation, which will provide carrier materials for the development of next-generation quantum devices based on novel spin states.

[0003] K2Cu3Ge5O 14 It is a quantum magnetic material system with an effective spin S=1 / 2 quasi-one-dimensional spin chain structure, in which magnetic Cu 2+ Ions bridged via the Cu-O-Cu pathway to form spin trimers, which arrange themselves in a quasi-one-dimensional spin chain structure. Adjacent Cu atoms within the trimer... 2+ Two equal-sized Cu-Cu bonds and head-and-tail Cu bonds are formed. 2+ The interaction forms a relatively long Cu-Cu bond, which introduces competitive frustration behavior and can induce rich quantum magnetic phenomena. In this material system, the large differences in ionic radii among cations such as K, Cu, and Ge make mixed site occupation difficult, and the ordered occupancy of magnetic ions allows for the exploration of the low-dimensional physics of the essential magnetic lattice structure.

[0004] Currently, regarding K2Cu3Ge5O 14 Methods for preparing single crystals are only reported in a few documents. For example, Monge et al. reported the growth of K2Cu3Ge5O using a flux method. 14 Single crystal method ( Chemistry of Materials (1926-1930), which uses GeO2, CuO and K2HPO4 as raw materials, mixed in a molar ratio of Ge:Cu:K=2:1:1, with KCl as flux, the mixture is placed in a nickel crucible and heated to 900℃ to melt, and then cooled to 850℃ at a rate of 1℃ / h, finally obtaining K2Cu3Ge5O 14 Single crystal. However, this approach has the following obvious drawbacks: (1) Poor crystal quality: The K2Cu3Ge5O prepared by this method 14 The single crystal size is extremely small, only 0.1×0.1×0.01mm, which does not meet the requirements for crystal size in performance testing and device applications.

[0005] (2) Impurity phase interference: This scheme uses K2HPO4 as a raw material, which will introduce P into the reaction system. 5+ Cations, during crystal growth, P 5+ It readily reacts with Cu in the system 2+ and K + The reaction produces potassium copper pyrophosphate (K₂CuP₂O₇) and potassium copper tetramethoxyphosphate (K₂CuP₄O₇). 12 Phosphorus-containing impurities such as phosphorus are present. Furthermore, the nickel crucible used in this scheme is prone to oxidation and corrosion at 900℃, further affecting product purity and yield.

[0006] Darren Carone et al. Crystal Growth & Design (2022, 22, 3319-3325) reported on the relationship with K2Cu3Ge5O 14 Single-crystal isomorphic Rb2Cu3Ge5O 14 and Cs2Cu3Ge5O 14 It is a single crystal, but its single crystal size is small (about 0.5×0.1×0.1mm) and there are impurities, so the intrinsic magnetic ground state behavior of the single crystal material cannot be observed.

[0007] Therefore, there is an urgent need to provide a method for obtaining large-size, high-purity K2Cu3Ge5O 14 Methods for preparing single-crystal materials. Summary of the Invention

[0008] To address the shortcomings of existing technologies, the purpose of this application is to provide a quantum magnetic material K2Cu3Ge5O 14 The method for preparing single crystals aims to solve the problems of K2Cu3Ge5O prepared by existing methods. 14 Single crystals are small in size and contain impurities, which makes them unsuitable for the requirements of physical property testing and device applications.

[0009] To achieve the above objectives, in a first aspect, this application provides a quantum magnetic material K2Cu3Ge5O 14 The method for preparing single crystals includes the following steps: S1. K2CO3, CuO, GeO2 and flux KCl are mixed to obtain a mixture; S2. Place the above mixture in a platinum crucible, seal it, and then heat and keep it at that temperature. S3. Cool the system to precipitate K2Cu3Ge5O 14 Single crystals are formed and naturally cooled to room temperature to obtain a molten ingot containing single crystals; S4. Remove the flux from the above-mentioned single-crystal-containing molten block to obtain the quantum magnetic material K2Cu3Ge5O. 14 Single crystal.

[0010] Preferably, in step S1, the molar ratio of K2CO3, CuO, GeO2, and KCl is 7:21:35:(100~200).

[0011] Preferably, in step S2, the heating temperature is 900℃~950℃.

[0012] Preferably, in step S2, the heat preservation time is 24~48h.

[0013] Preferably, in step S3, the cooling rate is ≤5℃ / h, and the temperature is reduced to 600℃~800℃ before natural cooling.

[0014] More preferably, the cooling rate is ≤2.5℃ / h.

[0015] Preferably, step S4 includes the following steps: soaking the above-mentioned single-crystal-containing molten metal in a solvent to dissolve the residual flux, followed by separation and drying to obtain the quantum magnetic material K2Cu3Ge5O. 14 Single crystal.

[0016] Secondly, this application provides a quantum magnetic material K2Cu3Ge5O 14 The single crystal was obtained using the above-described preparation method.

[0017] In summary, the technical solutions conceived in this application have the following main technical advantages compared with the prior art: (1) The quantum magnetic material K2Cu3Ge5O provided in this application 14 The method for preparing single crystals uses K2CO3, CuO, and GeO2 as raw materials and KCl as a single flux, thus completely avoiding P at the source. 5+ The introduction of other cations eliminates the formation of phosphorus-containing impurities such as K2CuP2O7, enabling the preparation of pure-phase K2Cu3Ge5O. 14 Single crystal.

[0018] (2) By adjusting the ratio of flux KCl to raw materials and the cooling rate, this application can stably crystallize high-quality single crystals at the millimeter level, with a maximum size of 4×1.5×0.4mm, which fully meets the requirements of physical performance testing such as magnetic measurement and specific heat measurement for crystal size, and overcomes the defect of crystal size being too small to be practically applied in the prior art.

[0019] (3) The millimeter-sized K2Cu3Ge5O prepared in this application 14Single crystals possess unique low-dimensional spin band gaps and low-temperature magnetic ordering behavior, making them ideal model materials for studying the quantum magnetism, spin excitation spectra, and quantum critical behavior of trimer chains. Furthermore, based on the aforementioned spin band gap and low-temperature magnetic ordering behavior, the K₂Cu₃Ge₅O₂ prepared in this application… 14 Single crystals hold promise for the fabrication of quantum computing devices, spintronic devices, or low-temperature magnetic refrigeration devices, providing a core material foundation for the development of these quantum devices and demonstrating promising application prospects. Attached Figure Description

[0020] Figure 1 The quantum magnetic material K2Cu3Ge5O provided in this application 14 A schematic diagram of the process for preparing single crystals; Figure 2 The K2Cu3Ge5O prepared in Example 1 of this application 14 A schematic diagram of the morphology of a single crystal; Figure 3 The K2Cu3Ge5O prepared in Example 1 of this application 14 A schematic diagram of the crystal structure of a single crystal; where (a) is the unit cell structure and (b) is a single layer of Cu in the unit cell. 2+ The connection channel with nonmagnetic ions, the content (c) is the Cu-Cu interaction to form a trimer chain structure; Figure 4 The K2Cu3Ge5O prepared in Example 1 of this application 14 X-ray diffraction pattern of powder refined from single crystal grinding; Figure 5 The K2Cu3Ge5O prepared in Example 1 of this application 14 Magnetization curves of single crystals; wherein, content (a) is the magnetic susceptibility curve and the reciprocal curve of magnetic susceptibility along the b* and c* directions in the temperature range of 1.8K~300K, and content (b) is an enlarged view of the magnetic susceptibility curve in the low temperature region. Figure 6 The K2Cu3Ge5O prepared in Example 1 of this application 14 The magnetization intensity of a single crystal along the b* and c* directions as a function of magnetic field at a temperature of 2K; Figure 7 The K2Cu3Ge5O prepared in Example 1 of this application 14 Specific heat curves of single crystals under zero magnetic field and at temperatures ranging from 0.1 K to 50 K; Figure 8 The K2Cu3Ge5O prepared in Example 2 of this application 14 A schematic diagram of the morphology of a single crystal; Figure 9 The K2Cu3Ge5O prepared in Example 3 of this application 14A schematic diagram of the morphology of a single crystal; Figure 10 The K2Cu3Ge5O prepared in Example 4 of this application 14 A schematic diagram of the morphology of a single crystal; Figure 11 The K2Cu3Ge5O prepared in Example 5 of this application 14 A schematic diagram of the morphology of a single crystal; Figure 12 The K2Cu3Ge5O prepared in Example 6 of this application 14 A schematic diagram of the morphology of a single crystal. Detailed Implementation

[0021] To make the objectives, technical solutions, and advantages of this application clearer, the following detailed description is provided in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are merely illustrative and not intended to limit the scope of this application.

[0022] In the description of this application, it should be understood that the term "and / or" describes a relationship between related objects, indicating that three relationships can exist. For example, A and / or B can represent: A existing alone, A and B existing simultaneously, or B existing alone. The symbol " / " in this document indicates that the related objects are in an "or" relationship; for example, A / B means A or B.

[0023] In the description of the embodiments in this application, the words "exemplary" or "for example" are used to indicate that they are examples, illustrations, or descriptions. Any embodiment or design that is described as "exemplary" or "for example" in the embodiments of this application should not be construed as being more preferred or advantageous than other embodiments or design options. Specifically, the use of the words "exemplary" or "for example" is intended to present the relevant concepts in a specific manner.

[0024] In the description of the embodiments in this application, unless otherwise stated, "multiple" means two or more.

[0025] like Figure 1 As shown, this application provides a quantum magnetic material K2Cu3Ge5O 14 The method for preparing single crystals includes the following steps: S1. K2CO3, CuO, GeO2 and flux KCl are mixed to obtain a mixture; S2. Place the above mixture in a platinum crucible, seal it, heat and melt it, and keep it at the temperature. S3. Cool the system to precipitate K2Cu3Ge5O 14 Single crystals are formed and naturally cooled to room temperature to obtain a molten ingot containing single crystals; S4. Remove the flux from the above-mentioned single-crystal-containing molten block to obtain the quantum magnetic material K2Cu3Ge5O. 14 Single crystal.

[0026] In some embodiments, in step S1, the molar ratio of K2CO3, CuO, GeO2, and KCl is 7:21:35:(100~200).

[0027] In some embodiments, in step S2, the heating and melting temperature is 900°C to 950°C, and the holding time is 24 to 48 hours. For example, the heating and melting temperature can be 900°C, 925°C, 950°C, etc., and the holding time can be 24 hours, 36 hours, 48 ​​hours, etc. This process helps the raw materials to fully melt and mix with the flux, facilitating single crystal growth.

[0028] In some implementations, in step S3, the temperature is lowered to 600°C to 800°C and then allowed to cool naturally. For example, the temperature can be lowered to 600°C, 650°C, 700°C, 750°C, or 800°C.

[0029] In some embodiments, the cooling rate in step S3 is ≤5℃ / h. For example, the cooling rate can be 0.5℃ / h, 1℃ / h, 1.5℃ / h, 2℃ / h, 2.5℃ / h, 3℃ / h, 3.5℃ / h, 4℃ / h, 4.5℃ / h, 5℃ / h, etc. The quantum magnetic material K2Cu3Ge5O prepared at this cooling rate... 14 The length of a single crystal is greater than 1 mm.

[0030] In a preferred embodiment, the cooling rate is ≤2.5℃ / h. The quantum magnetic material K2Cu3Ge5O prepared at this cooling rate... 14 The length of a single crystal is no less than 1.5 mm, and can even reach 4 mm.

[0031] In some embodiments, the flux in the molten ingot can be removed by solvent immersion in step S4. Specifically, step S4 includes the following steps: immersing the molten ingot containing the single crystal in a solvent to dissolve the residual flux, followed by separation and drying to obtain the quantum magnetic material K2Cu3Ge5O. 14 Single crystal.

[0032] It is understood that this application does not have any particular limitation on the type of solvent mentioned above, and solvents known in the art that can dissolve KCl but not K2Cu3Ge5O can be used. 14Solvent for the single crystal. For example, the solvent can be deionized water, dilute acid (such as dilute hydrochloric acid, dilute nitric acid, or dilute sulfuric acid, preferably with a concentration of 0.1~2 mol / L), or a mixed solvent of organic solvent (such as ethanol or acetone) and deionized water. The amount of solvent should be sufficient to completely submerge the fused block containing the single crystal, typically 2~5 times the volume of the fused block. The soaking time can be adjusted according to the temperature and stirring conditions; generally, soaking at room temperature for 6~24 hours is sufficient to fully dissolve the flux. If necessary, heating to 40℃~60℃ can be used to accelerate dissolution.

[0033] In some embodiments, the separation methods include, but are not limited to, filtration and centrifugation. In some embodiments, the separated solids may be washed 1 to 3 times with a small amount of solvent to remove residual flux from the surface.

[0034] In some embodiments, the drying methods described above include, but are not limited to, natural air drying, drying in a forced-air drying oven, or vacuum drying. Those skilled in the art can adaptively adjust the drying temperature, time, etc., according to the actual selected drying process, all of which are within the scope of protection of this application.

[0035] This application uses the above-described preparation method to obtain K2Cu3Ge5O 14 The single crystals are elongated, bluish-green in color, with distinct axial protrusions, high purity, and large size, meeting the requirements for precise physical property measurements. Based on this, this application also provides a quantum magnetic material, K₂Cu₃Ge₅O₂. 14 The single crystal was obtained using the above-described preparation method.

[0036] The K2Cu3Ge5O obtained in this application 14 The spin band gap and low-temperature magnetic ordering behavior of single crystals make them ideal model materials for studying the quantum magnetism, spin excitation spectrum, and quantum critical behavior of trimer chains.

[0037] The following are examples and comparative examples: Example 1 The K2Cu3Ge5O provided in this embodiment 14 The method for preparing single crystals includes the following steps: (1) Weigh the raw materials K2CO3, CuO, GeO2 and flux KCl in a molar ratio of 7:21:35:100, then grind them thoroughly in an agate mortar for 6 hours to make them evenly mixed and obtain a mixed powder.

[0038] (2) The above mixed powder was placed into a platinum crucible, sealed, and then placed in a muffle furnace. The temperature was raised to 900℃ and held for 24 hours. Subsequently, the temperature was slowly lowered to 800℃ at a rate of 0.5℃ / h to precipitate K2Cu3Ge5O. 14 Single crystals are formed and then naturally cooled to room temperature to obtain a fused mass containing single crystals.

[0039] (3) Remove the crucible, soak and wash the molten block containing the single crystal repeatedly with deionized water at 50℃~60℃ to fully dissolve the flux KCl. After solid-liquid separation and drying, the target single crystal material K2Cu3Ge5O is obtained. 14 .

[0040] Figure 2 The K2Cu3Ge5O prepared in this embodiment 14 The morphology diagram of the single crystal shows that each small square represents 1 mm × 1 mm. It can be seen that the K2Cu3Ge5O crystal prepared in this embodiment... 14 The single crystal is elongated, bluish-green in color, and has a distinct convex axis. Its dimensions are approximately 1.5 × 0.8 × 0.4 mm.

[0041] Figure 3 The K2Cu3Ge5O prepared in this embodiment 14 A schematic diagram of the crystal structure of a single crystal, from... Figure 3 Content (a), Figure 3 Content (b) Figure 3 As can be seen from content (c), K2Cu3Ge5O 14 Magnetic Cu in single crystal 2+ Ions form unique trimer chains, with non-magnetic K atoms between the chains. + and Ge 4+ Separate.

[0042] Figure 4 The K2Cu3Ge5O prepared in this embodiment 14 The refined X-ray diffraction pattern of the powder after grinding the single crystal shows that it perfectly matches the standard pattern and has no impurity peaks, indicating that the product is a high-purity phase.

[0043] Figure 5 The K2Cu3Ge5O prepared in this embodiment 14 The magnetization curve of a single crystal is derived from... Figure 5 Content (a), Figure 5 Content (b) shows that K2Cu3Ge5O 14 The single crystals exhibit typical low-dimensional magnetic characteristics at 16K and 3.9K.

[0044] Figure 6 The K2Cu3Ge5O prepared in this embodiment 14 The curves showing the magnetization intensity along the b* and c* directions of a single crystal as a function of magnetic field at a temperature of 2K. Figure 7 The K2Cu3Ge5O prepared in this embodiment 14 The specific heat curves of the single crystal at zero magnetic field and temperatures ranging from 0.1 K to 5 K further confirm the K₂Cu₃Ge₅O₂14 Magnetic anisotropy of single crystals and magnetic order transition behavior near 4K.

[0045] Comparative Example 1 The K2Cu3Ge5O provided in this comparative example 14 The preparation method of the single crystal is the same as in Example 1, except that: PbO is used as the flux, the melt is rinsed with deionized water and then mechanically peeled off.

[0046] No crystal precipitation was observed after the experiment.

[0047] Comparative Example 2 The K2Cu3Ge5O provided in this comparative example 14 The preparation method of the single crystal is the same as in Example 1, except that: PbF2 is used as the flux, the melt is rinsed with deionized water and then mechanically peeled off.

[0048] No crystal precipitation was observed after the experiment.

[0049] Comparative Example 3 The K2Cu3Ge5O provided in this comparative example 14 The preparation method of the single crystal is the same as in Example 1, except that the molar ratio of K2CO3, CuO, GeO2 and KCl is 7:21:35:75.

[0050] No crystal precipitation was observed after the experiment.

[0051] Comparative Example 4 The K2Cu3Ge5O provided in this comparative example 14 The preparation method of the single crystal is the same as in Example 1, except that the molar ratio of K2CO3, CuO, GeO2 and KCl is 7:21:35:300.

[0052] No crystal precipitation was observed after the experiment.

[0053] Example 2 The K2Cu3Ge5O provided in this embodiment 14 The method for preparing single crystals differs from that in Example 1 in that: In step (1), the molar ratio of K2CO3, CuO, GeO2, and KCl is 7:21:35:125; In step (2), the temperature is slowly reduced to 750℃ at a rate of 1℃ / h.

[0054] The K2Cu3Ge5O prepared 14 The size of the single crystal is approximately 2 × 0.8 × 0.4 mm. Figure 8 ).

[0055] Example 3 The K2Cu3Ge5O provided in this embodiment 14 The method for preparing single crystals differs from that in Example 1 in that: In step (1), the molar ratio of K2CO3, CuO, GeO2, and KCl is 7:21:35:150, and the grinding time is 7 hours. In step (2), the temperature is raised to 925℃ and held for 36 hours, and then slowly cooled to 700℃ at a rate of 1.5℃ / h.

[0056] The K2Cu3Ge5O prepared 14 The size of the single crystal is approximately 4 × 1.5 × 0.4 mm. Figure 9 ).

[0057] Example 4 The K2Cu3Ge5O provided in this embodiment 14 The method for preparing single crystals differs from that in Example 1 in that: In step (1), the molar ratio of K2CO3, CuO, GeO2, and KCl is 7:21:35:175, and the grinding time is 7 hours. In step (2), the temperature is raised to 925℃ and held for 36 hours, and then slowly cooled to 650℃ at a rate of 2℃ / h.

[0058] The K2Cu3Ge5O prepared 14 The size of the single crystal is approximately 1.5 × 1 × 0.4 mm. Figure 10 ).

[0059] Example 5 The K2Cu3Ge5O provided in this embodiment 14 The method for preparing single crystals differs from that in Example 1 in that: In step (1), the molar ratio of K2CO3, CuO, GeO2, and KCl is 7:21:35:200, and the grinding time is 8 hours. In step (2), the temperature is raised to 950℃ and held for 48 hours, and then slowly cooled to 600℃ at a rate of 2.5℃ / h.

[0060] The K2Cu3Ge5O prepared 14 The size of a single crystal is approximately 2 × 1 × 0.4 mm. Figure 11 ).

[0061] Example 6 The K2Cu3Ge5O provided in this embodiment 14 The method for preparing single crystals differs from that in Example 1 in that: In step (1), the molar ratio of K2CO3, CuO, GeO2, and KCl is 7:21:35:200, and the grinding time is 8 hours. In step (2), the temperature is raised to 950℃ and held for 48 hours, and then slowly cooled to 600℃ at a rate of 5℃ / h.

[0062] The K2Cu3Ge5O prepared 14 The size of the single crystal is approximately 1.1 × 0.2 × 0.2 mm. Figure 12 ).

[0063] Compared to existing methods, the preparation method provided in this application uses K2CO3, CuO, and GeO2 as raw materials and KCl as a single flux, thus eliminating P at the source. 5+ The introduction of other cations prevents the formation of phosphorus-containing impurities such as K₂CuP₂O₇. Furthermore, by controlling the ratio of flux KCl to the raw materials and the cooling rate, high-quality single crystals in the millimeter range (up to 4 × 1.5 × 0.4 mm) can be stably crystallized, fully meeting the requirements for magnetic and specific heat measurements. Simultaneously, the obtained large-size K₂Cu₃Ge₅O₇... 14 Single crystals possess spin band gaps and low-temperature magnetic ordering behavior, making them ideal model materials for studying the quantum magnetism, spin excitation spectra, and quantum critical behavior of trimer chains. Furthermore, based on the aforementioned spin band gaps and low-temperature magnetic ordering behavior, the K₂Cu₃Ge₅O₂ prepared in this application… 14 Single crystals hold promise for the fabrication of quantum computing devices, spintronic devices, or low-temperature magnetic refrigeration devices, and have promising applications.

[0064] Those skilled in the art will readily understand that the above description is merely a preferred embodiment of this application and is not intended to limit this application. Any modifications, equivalent substitutions, and improvements made within the spirit and principles of this application should be included within the protection scope of this application.

Claims

1. A quantum magnetic material K2Cu3Ge5O 14 A method for preparing single crystals, characterized in that, Includes the following steps: S1. Mix K2CO3, CuO, GeO2 and flux KCl to obtain a mixture; S2. Place the mixture in a platinum crucible, seal it, and then heat and keep it warm. S3. Cool the system to precipitate K2Cu3Ge5O 14 Single crystals are formed and naturally cooled to room temperature to obtain a molten ingot containing single crystals; S4. Remove the flux from the single-crystal-containing molten metal to obtain the quantum magnetic material K2Cu3Ge5O. 14 Single crystal.

2. The preparation method according to claim 1, characterized in that, In step S1, the molar ratio of K2CO3, CuO, GeO2, and KCl is 7:21:35:(100~200).

3. The preparation method according to claim 1, characterized in that, In step S2, the heating temperature is 900℃~950℃, and / or the heat preservation time is 24~48h.

4. The preparation method according to claim 1, characterized in that, In step S3, the cooling rate is ≤5℃ / h, and the temperature is reduced to 600℃~800℃ before natural cooling.

5. The preparation method according to claim 4, characterized in that, The cooling rate is ≤2.5℃ / h.

6. The preparation method according to claim 1, characterized in that, Step S4 includes the following steps: immersing the single-crystal-containing molten metal in a solvent to dissolve the residual flux, followed by separation and drying to obtain the quantum magnetic material K2Cu3Ge5O. 14 Single crystal.

7. A quantum magnetic material K2Cu3Ge5O 14 Single crystal, characterized in that, It is obtained by the preparation method according to any one of claims 1 to 6.